The relationship between personality disorders and quality of life in adolescent outpatients - Korsgaard, Hans Ole; Torgersen, Svenn; Wentzel-Larsen, Tore; Ulberg, Randi (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2015)
Background: During recent years, there has been an increasing focus on the benefits of the early detection and treatment of personality disorders in adolescents. Previous studies of adults have shown that the number of personality disorder criteria met is negatively correlated with a patient’s quality of life and general functioning.Objective: The aim of the present study was to investigate the prevalence of personality disorders, particularly with regard to the correlation between the number of personality disorder criteria fulfilled and self-perceived quality of life. Distribution according to gender and age in a clinical sample of adolescent outpatients were also considered.Method: This study included 153 adolescents between the ages of 14 and 17 years who were referred to a mental health outpatient clinic. Personality disorders were assessed using the Structured Interview for DSM-IV Personality. Quality of life was assessed using the Youth Quality of Life Instrument - Research Version, which is a 41-item questionnaire that covers broad aspects of quality of life. Axis I disorders were assessed using the Mini International Neuropsychiatric Interview.Results: Results demonstrated that 21.6% of the adolescents met the diagnostic criteria for at least one personality disorder. A relationship between the number of personality disorder criteria met and reduced quality of life was found. No significant gender differences with regard to the prevalence of each of the personality disorders were revealed. Adjustment for the presence of Axis I disorders did not appreciably affect these findingsConclusion: The present study indicates that reduced quality of life as a result of the number of personality disorder criteria met affects adolescents in much the same way that it does adults. This further emphasizes the clinical importance of including quality of life assessment as part of the general diagnostic procedures used with adolescents.